SERUM LEVELS OF C-REACTIVE PROTEIN, COMPLEMENT 3 AND COMPLEMENT 4 IN IRAQI DIABETIC PATIENTS ON METFORMIN THERAPY: Pharmaceutical Science-Clinical Laboratories Sciences - MUHANNAD SHWEASH; HATEM M. HADEED; YASIR M. FARHAN; THULFIQAR FAWWAZ MUTAR (International Journal of Life Science and Pharma Research, 2022)
Metformin is considered as an oral anti-diabetes agent. It is regularly used as a first-drug for the controlling of type-2 Diabetes Mellitus (T2DM). However, we aimed to evaluate whether the inflammatory biomarkers C - reactive protein (CRP), Complement 3 (C3) and Complement 4 (C4) levels are affected by metformin therapy in (T2DM) patients. Data from 150 male patients were classified into five groups (40 diabetics metformin users only, 40 diabetics without treatment, 25 diabetic insulin users only, 25 diabetic insulin plus metformin users and 20 nondiabetic healthy groups). The age ranged from 40-70 years old; samples were collected from patients who underwent treatment at National Center for Diabetes Research and Treatment/Baghdad between the periods of October 2016 and June 2017. Blood sampling was collected separated and determined by using immunoassays. Our study revealed that serum levels of C - reactive protein, C3 and C4 significantly increased in patients with (T2DM) without metformin treatment (Uncontrolled). Serum levels of all indicated markers were markedly reduced in the metformin-treated group. Patients using insulin alone showed marked reduction in C4 level. While in patients using both insulin and metformin, C - reactive protein and C3 were highly reduced than C4 which was approximately 50 % of decrement. Study outcomes demonstrated an elevation of some inflammatory biomarkers in uncontrolled diabetic patients. Metformin has a potential role in alleviating these indicated biomarkers.